Plaque and remodeling markers in coronary thrombi. (14th October 2021) - Nordeng, J; Helseth, R; Aakra, S; Hoffmann, P; Schandiz, H; Roald, B; Bendz, B; Arnesen, H; Solheim, S; Seljeflot, I
Abstract: Background: Matrix Metalloproteinases (MMPs) and their inhibitors are considered to be of importance in development of atherosclerotic coronary artery disease. MMP-9 has been associated with unstable atherosclerotic plaques and rupture, as well as left ventricular remodeling after myocardial infarction (MI), whereas MMP-2 seems to be more related to progression of stable plaques. MMP activity is modulated by Tissue Inhibitors of Metalloproteinases (TIMPs). TIMP-1 has been associated with cardiac remodeling post MI, and TIMP-2 has been discussed to inhibit plaque development and destabilization. The extracellular MMP Inducer, EMMPRIN, stimulates both MMPs and TIMPs, and has been found upregulated on the surface of monocytes in patients with acute MI, and associated with MMP-9 activity. Purpose: To study whether genes encoding MMP-2, MMP-9, TIMP-1, TIMP-2 and EMMPRIN are expressed in coronary thrombi and in circulating leukocytes from STEMI patients, and whether these are related to the degree of myocardial injury measured by troponin T, and time from symptoms to PCI. Methods: Intracoronary thrombi were aspirated from 33 patients with ST-elevation myocardial infarction (STEMI) treated with primary PCI. The thrombi were snap-frozen in RNA-later solution for gene expression analyses. Peripheral blood samples with Pax-gene tubes were drawn at end of the PCI procedure. RNA was isolated from the thrombi and leukocytes, and the actual genes relatively quantified by RT PCR. Peak troponin T was collected from clinical records. Results: Genes coding for the five different markers were present in 84–100% of the thrombi. Median peak troponin T was 3434 m/L. The expression of TIMP-1 in the thrombi correlated significantly to peak troponin T (r=0.393, p=0.026), and dividing peak troponin T values into quartiles, the median value of TIMP-1 mRNA in Q4 was 2.5-fold higher compared to Q1–3 (p=0.107). Peak troponin T also correlated to the expression of TIMP-1 in circulating leukocytes (r=0.469, p=0.006), and in Q4 of troponin T, the median value was 1.6-fold higher compared to Q1–3 (p=0.056). There were no significant correlations between the other measured genes and troponin T, and also no associations of any genes expressed in the thrombi or in circulating leukocytes to time from symptom to PCI (median 152 min). Conclusion: Genes coding for MMP-2, MMP-9, TIMP-1, TIMP-2 and EMMPRIN were highly expressed in human coronary thrombi. The positive correlation between peak troponin T and the expression of TIMP-1 both in thrombi and in circulating leukocytes at time of PCI in patients with STEMI, may indicate that the role of TIMP-1 is important in cardiac remodeling immediately post-MI. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Stein Erik Hagens Foundation for Clinical Heart Research